NSTX/NSTX-U theory, modeling and analysis results. (5th June 2019) - Kaye, S.M.; Battaglia, D.J.; Baver, D.; Belova, E.; Berkery, J.W.; Duarte, V.N.; Ferraro, N.; Fredrickson, E.; Gorelenkov, N.; Guttenfelder, W.; Hao, G.Z.; Heidbrink, W.; et al.
Abstract: The mission of the spherical tokamak NSTX-U is to explore the physics that drives core and pedestal transport and stability at high- and low collisionality, as part of the development of the spherical tokamak (ST) concept towards a compact, low-cost ST-based pilot plant. NSTX-U will ultimately operate at up to 2 MA and 1 T with up to 12 MW of neutral beam injection power for 5 s. NSTX-U will operate in a regime where electromagnetic instabilities are expected to dominate transport, and beam-heated NSTX-U plasmas will explore a portion of energetic particle parameter space that is relevant for both -heated conventional and low aspect ratio burning plasmas. NSTX-U will also develop the physics understanding and control tools to ramp-up and sustain high performance plasmas in a fully-noninductive fashion. NSTX-U began research operations in 2016, but a failure of a divertor magnetic field coil after ten weeks of operation resulted in the suspension of operations and initiation of recovery activities. During this period, there has been considerable work in the area of analysis, theory and modeling of data from both NSTX and NSTX-U, with a goal of understanding the underlying physics to develop predictive models that can be used for high-confidence projections for both ST and higher aspect ratio regimes. These studies have addressed issues in thermal plasma transport, macrostability, energetic particlet-driven instabilities at ion-cyclotron frequencies and below, and edge and divertor physics.